Le trio hergéen : un tournant dans « Les aventures de Tintin » - Chéron, Sophie (Wydawnictwo Naukowe UAM, 2012)
Before Captain Haddocks’ and Professor Calculus’ appearance in "The Crab with the Golden Claws" (eighth album, 1941) and "Red Rackham’s Treasure" (eleventh album, 1944) Tintin doesn’t have strong links with the other characters. His youth, dynamism and resourcefulness are his only characteristics – he has no past, no name, no family, no occupational ties. The two new friends Hergé gives him provide the last ten albums of The Adventures more consistency, humor, and a proper space which were missing until then.
The Hergéan trio: A turning point in "The Adventures of Tintin"
Keywords: Comic strips; Hergé; Tintin; Identity; Narrative function